Pengaruh Customer Relationship Management, Image, Dan Kepercayaan Terhadap Kepuasan Konsumen (Studi Kasus Pada Restoran Alka Kitchen Kota Pasuruan, Jawa Timur) - Karina Widyaswari Iin Kusumawati; Nur Hidayati; M. Khoirul ABS (UNIVERSITAS ISLAM MALANG, 2021)
AbstractThis research was conducted to determine the effect of Customer Relationship Management, Image, and Trust on Customer Satisfaction (Case Study at Alka Kitchen Restaurant, Pasuruan City, East Java). This research uses explanatory research and a quantitative approach. Sugiyono theory, the method used to find the number of samples in this study is to use the Slovin formula and it is known that the number of samples is 109 respondents. The results of this study are that there is a simultaneous influence between Customer Relationship Management (CRM), Image and Trust on Customer Satisfaction at Alka Kitchen Restaurant, Pasuruan City, East Java, Variable Customer Relationship Management (CRM). ), has an effect on consumer satisfaction at Alka Kitchen Restaurant in Pasuruan City, East Java, variable image affects customer satisfaction at Alka Kitchen restaurant in Pasuruan city, East Java, and trust variable affects customer satisfaction at Alka Kitchen restaurant in Pasuruan city, East Java. Keywords: Customer Satisfaction, Customer Relationship Management, Image, Trust.